2016
DOI: 10.1038/tpj.2016.63
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of ATP7b, BRCA1, BRCA2, PARP1, UIMC1 (RAP80), HOXA9, DAXX, TXN (TRX1), THBS1 (TSP1) and PRR13 (TXR1) genes in patients with epithelial ovarian cancer who received platinum-taxane first-line therapy

Abstract: To evaluate the predictive value of genes involved in resistance to platinum-taxane chemotherapy in patients with epithelial ovarian cancer (EOC). Microdissected formalin-fixed tumoral samples from 187 EOC patients' primary tumors (90 and 97 samples from matched patients in the experimental and validation sets, respectively) were analyzed. All specimens were analyzed for ATP7b, BRCA1, BRCA2, PARP1, UIMC1(RAP80), HOXA9, DAXX, TXN (TRX1), THBS1 (TSP1) and PRR13 (TXR1) mRNA expression by quantitative real-time PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 40 publications
1
12
0
2
Order By: Relevance
“…53,54 It has also been shown that overexpression of BRIP1 protein correlated with an increased cell proliferation rate, 54 which may contribute to earlier tumor recurrence. 55,56 Thus, both our analysis and published data indicate that high level of BRIP1 in tumor cells is an unfavorable factor, especially in patients treated with DNA damaging compounds.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…53,54 It has also been shown that overexpression of BRIP1 protein correlated with an increased cell proliferation rate, 54 which may contribute to earlier tumor recurrence. 55,56 Thus, both our analysis and published data indicate that high level of BRIP1 in tumor cells is an unfavorable factor, especially in patients treated with DNA damaging compounds.…”
Section: Discussionmentioning
confidence: 61%
“…To date, there is no consensus on the impact of BRCA1 expression on ovarian cancer patients' outcome, and there are few studies on the clinical importance of BRCA2 expression. Several studies have indicated the lack of relationship between the BRCA1/2 expression and the response to TP-treatment, 56,57 while others have reported that low level of the BRCA1 mRNA positively influenced prognosis (OS) of the PC-treated patients 58 , and the TP-treated patients with the residual tumor less than 2 cm. 59 In some other cancers, high BRCA1 gene expression has been considered to be a negative prognostic and/or predictive factor, [60][61][62] while high expression of BRCA2 at mRNA level in breast cancer patients had a negative impact on docetaxel response.…”
Section: Dfsmentioning
confidence: 99%
“…Making deeper understanding of the role of cell cycle proteins, including revealing their function mechanisms and finding their relevant upstream or downstream targets, could help us to discover more valuable biomarkers. Fortunately, the development of biotechnology, like microarray, transcriptome sequencing, and proteomics, has provided an advanced way to get the nearly all gene expression information during all stages for any human genomes and lots of potential therapeutic targets have been excavated, including AFP 14 , BCR-ABL 15 , BRCA1/BRCA2 16 , EGFR 17 , HER2 18 and so on.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, CAP did not affect the net intracellular level of Tx (i.e., transport of Tx across the plasma membrane after CAP treatment was not changed significantly). In contrast, the expression of genes previously known to be responsible for drug resistance, such as Bcl2L13 (1.86-fold decrease) [26,27] and HOXA9 (2.14-fold increase) [28], was changed by CAP. This discrepancy explains the complication of drug transport in the MCF-7/TxR cells.…”
Section: Discussionmentioning
confidence: 75%